2008
DOI: 10.1016/j.cbpa.2007.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Unearthing the roots of the terpenome

Abstract: SummaryAlthough terpenoid synthases catalyze the most complex reactions in biology, these enzymes appear to play little role in the chemistry of catalysis other than to trigger the ionization and chaperone the conformation of flexible isoprenoid substrates and carbocation intermediates through multi-step reaction cascades. Fidelity and promiscuity in this chemistry, i.e., whether a terpenoid synthase generates one or several products, depends on the permissiveness of the active site template in chaperoning eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
198
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 289 publications
(204 citation statements)
references
References 57 publications
5
198
0
1
Order By: Relevance
“…S3B). This strongly supports the model that terpene synthases mainly dictate reaction outcome by sterically restricting their substrate and discrete reaction intermediates to a subset of possible productive conformations (template model) (22,24). Moreover, it demonstrates differing binding modes followed by nonnative cyclization characteristics for substrate analogs that hamper the correct prediction of important structure-function relationships in class I terpene synthases.…”
Section: Txs•ggpp Complex: Evolutionarily Conserved Motifs Initiate Thesupporting
confidence: 73%
See 3 more Smart Citations
“…S3B). This strongly supports the model that terpene synthases mainly dictate reaction outcome by sterically restricting their substrate and discrete reaction intermediates to a subset of possible productive conformations (template model) (22,24). Moreover, it demonstrates differing binding modes followed by nonnative cyclization characteristics for substrate analogs that hamper the correct prediction of important structure-function relationships in class I terpene synthases.…”
Section: Txs•ggpp Complex: Evolutionarily Conserved Motifs Initiate Thesupporting
confidence: 73%
“…The lack of essential Y residues results in hydroxylated products as in the case of CBTS, which suggests an amino acid-assisted mechanism that provide control for water-assisted quenching products. We could further demonstrate by moleculardocking calculations that, in the initial reaction phase, the acyclic cation A can only assume a single conformation, which strongly argues for the template model (22). The data confirm the existence of a monocyclic cation B, specifically as in TXS-W753H deprotonation of C17 results in formation of CM.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…82 These studies confirmed the universal all-helical fold of the sesquiterpene and monoterpene synthases, and have provided detailed pictures of the organization of the active sites of these remarkable, synthetically versatile cyclases. 76,[83][84][85][86] Complementing and enriching these studies, Prof Dean J Tantillo (U. C. Davis) has deepened the understanding of the mechanisms and energetics of terpene cyclization reactions through detailed quantum chemical calculations of the reaction pathways linking carbocationic intermediates and transition state structures for a wide variety of terpene synthase-catalyzed reactions. [87][88][89][90][91] In spite of the substantial progress in cloning terpene synthases, the search for additional terpene synthase genes was seriously hindered by the exceptionally low levels of mutual sequence similarity among known terpene synthases, thus thwarting the routine application of homology-based cloning methods to this class of microbial proteins.…”
Section: Enzymology and Molecular Genetics Of Natural Product Biosyntmentioning
confidence: 99%